A sandwich structure water electrolysis composite diaphragm, preparation method and application

By adopting a sandwich sandwich structure, the existing alkaline electrolytic cell diaphragm has solved the shortcomings in energy consumption, cost, gas penetration and mechanical properties, and achieved high-efficiency, low-energy consumption, scratch resistance and low-plane resistance separator performance, suitable for zero-pole-distance electrolytic cells.

CN119239017BActive Publication Date: 2025-04-08SUZHOU XIBEIYOU HYDROGEN ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411766347.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-08
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The separators of existing alkaline electrolytic cells have problems in terms of high energy consumption, high cost, gas penetration and safety hazards, and the mechanical strength and scratch resistance of traditional composite membranes are not sufficient to meet the needs of zero-pole-distance electrolytic cells.

Method used

The electrolytic water-based composite separator with a sandwich sandwich structure includes a PTFE/polymer/inorganic nanoparticle composite porous layer as the first and third layers, and the intermediate layer is a polymer/inorganic nanoparticle composite porous layer. The mechanical and electrolytic properties of the separator are improved through specific preparation methods.

Benefits of technology

It realizes the efficient and low energy consumption performance of the diaphragm, enhances the surface scratch resistance and bending resistance, and reduces the surface resistance of the diaphragm. It is suitable for zero-pole-distance electrolytic cells, and improves the energy efficiency and market competitiveness of electrolyzing water hydrogen production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119239017B_ABST
    Figure CN119239017B_ABST
Patent Text Reader

Abstract

The invention discloses a sandwich structure water electrolysis composite diaphragm, a preparation method and application, the diaphragm is composed of a three-layer structure, the first layer is a PTFE / polymer / inorganic nanoparticle composite porous layer, the middle layer is a polymer / inorganic nanoparticle composite porous layer, and the third layer is a PTFE / polymer / inorganic nanoparticle composite porous layer. The configured casting liquid is first horizontally coated on the hydrophilic PTFE porous membrane, and then another layer of hydrophilic PTFE porous membrane is flattened on the PTFE porous membrane coated with the casting liquid, and a three-layer composite wet film is formed after standing; and the sandwich structure water electrolysis composite diaphragm is placed in a coagulation bath. The invention has a simple implementation process, and the operation steps are easy to repeat. Through the innovation of the composite membrane structure, the scratch resistance, bending resistance, tensile resistance and tear resistance of the diaphragm are enhanced, and a three-dimensional porous structure is formed at the same time, which can effectively reduce the diaphragm surface resistance and the hydrogen production energy consumption of the electrolyzer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water electrolysis membrane preparation, and in particular relates to a sandwich structure water electrolysis composite membrane, a preparation method and an application thereof. Background Art

[0002] Nowadays, human society has developed to a certain level, and the concept of energy conservation and environmental protection has become increasingly popular, but social life is still highly dependent on fossil energy. The non-renewable nature of fossil energy has caused the global energy crisis to be imminent. At the same time, the use of fossil energy is inevitably destructive to the natural environment. Therefore, with the increasingly serious environmental pollution, the energy volume is becoming increasingly exhausted, but the demand is growing significantly, the development of renewable and clean energy such as solar energy, wind energy, and hydropower is an important development direction. As a form of energy storage with high energy density and sustainable development, hydrogen has become a more ideal energy carrier at present. At the same time, the hydrogen production path of water electrolysis has the characteristics of high energy efficiency and low emissions. If water electrolysis is combined with renewable energy power generation, it can effectively reduce the cost of water electrolysis and enhance the market competitiveness of water electrolysis. Compared with renewable clean energy with greater volatility, hydrogen energy has the characteristics of cleanliness and efficiency, and as a secondary energy source, it is easy to prepare and store. Therefore, it is an inevitable trend for hydrogen energy, as a new century energy, to enter the historical stage.

[0003] At present, alkaline water electrolysis is the most mature, most widely used commercial method in the world, and has the greatest potential for large-scale application. Traditional alkaline electrolyzers use 10-30 wt% KOH electrolyte, with an operating pressure of 1.6-3.2 MPa, an operating temperature of 80-90°C, and an energy consumption of 4.5-5.0 kWh / Nm 3 H 2 Although alkaline water electrolysis hydrogen production technology has been widely used, it still has problems such as high energy consumption and high cost.

[0004] Alkaline electrolyzers have good advantages over PEM electrolyzers because they do not require precious platinum-based noble metal catalyst electrodes. However, alkaline electrolyzers currently generally use PPS cloth as a diaphragm. In addition to high energy consumption, its bubble point pressure is only 0.04~0.06 bar. It is difficult to avoid gas penetration through the diaphragm during the electrolysis process, resulting in a decrease in gas purity and even potential safety hazards. To overcome these shortcomings, advanced alkaline electrolyzers combine the advantages of traditional alkaline electrolyzers and PEM electrolyzers because they can use low-cost transition metal catalysts and have the same zero-gap structure as PEM electrolyzers. The zero-gap structure allows the membrane to fit tightly against the electrode. As the pressure changes dynamically during the operation of the electrolyzer, the surface of the diaphragm is severely worn. The traditional third-generation composite diaphragm (such as Agfa's ZIRFON UTP 500 / 220) is made of an alkali-resistant polymer woven mesh such as polyphenylene sulfide as the base, with high-temperature alkali-resistant polymer slurry coated on both sides. The composite diaphragm has poor surface mechanical strength and the polymer coating can easily fall off, resulting in poor gas barrier properties and even electrode short circuit. Therefore, this type of composite diaphragm is no longer suitable for zero-gap electrolyzers.

[0005] Therefore, developing a high-performance water electrolysis composite diaphragm with relatively simple production process, excellent high temperature resistance, strong alkali corrosion resistance and surface scratch resistance, and high efficiency and low energy consumption has become one of the technical problems that urgently need to be solved in this technical field. Summary of the invention

[0006] The purpose of the present invention is to solve the deficiencies of existing materials and technologies, and to provide a sandwich structure water electrolysis composite diaphragm, a preparation method and application. The present invention has a simple implementation process, simple and easy-to-repeat operation steps, and a wide range of applications. Through the innovation of the composite membrane structure, the surface scratch resistance and bending resistance of the diaphragm are enhanced, and the surface resistance of the diaphragm and the hydrogen production energy consumption of the electrolyzer are reduced.

[0007] A sandwich structure water electrolysis composite diaphragm comprises a first layer, an intermediate layer and a third layer which are composited into one body, wherein the first layer is a PTFE / polymer / inorganic nanoparticle composite porous layer with a thickness of 5 to 50 μm; the intermediate layer is a polymer / inorganic nanoparticle composite porous layer with a thickness of 100 to 400 μm; and the third layer is a PTFE / polymer / inorganic nanoparticle composite porous layer with a thickness of 5 to 50 μm.

[0008] A method for preparing a sandwich structure water electrolysis composite diaphragm is provided, comprising the following steps:

[0009] A: Lay the hydrophilic treated PTFE microporous membrane flat on a glass plate and fix the glass plate with a porous vacuum suction cup;

[0010] B: horizontally coating the milky white casting solution on the PTFE microporous membrane in step A, with the coating scraper spacing being 200-600 μm, to obtain a white wet film;

[0011] C: Another layer of hydrophilic treated PTFE microporous membrane is laid flat on the white wet membrane prepared in step B, and a scraper with a preset spacing of 200-600 μm is used to scrape the surface of the PTFE microporous membrane flat, and the surface is left to stand for 10-60 seconds to obtain a liquid wet membrane with a thickness of 200-600 μm;

[0012] D: Put the liquid wet film obtained in step C together with the glass plate into a primary coagulation bath for 2 to 30 minutes, the temperature of the coagulation bath is 0 to 60°C, the liquid wet film and the glass plate are separated in the primary coagulation bath, and the liquid wet film is initially cured in the primary coagulation bath to form a white film;

[0013] E: The white film obtained in step D is placed in a secondary coagulation bath for 5 to 30 minutes at a coagulation bath temperature of 10 to 60° C., and finally a sandwich structured water electrolysis composite diaphragm with a thickness of 150 to 500 μm is obtained.

[0014] Further, the contact angle between the hydrophilic PTFE microporous membrane described in step A and water is 0°~180°. The smaller the contact angle, the stronger the hydrophilicity. The film is sufficiently hydrophilic to ensure that the casting liquid is quickly immersed in the micropores of the PTFE film, thereby improving the bonding force of the interface between the two, and thus improving the scratch resistance of the diaphragm; at the same time, the better the hydrophilicity, the more hydrophilic the surface of the composite membrane is, which is beneficial to reducing the electrolysis energy consumption of the diaphragm, so the contact angle is preferably 0°; the thickness of the hydrophilic PTFE microporous membrane is 5~ 50μm, a microporous membrane that is too thin will have a serious electrostatic effect, affecting the smoothness of the coating, and a microporous membrane that is too thick will increase the overall thickness of the diaphragm, and a microporous membrane that is too thick generally has a low porosity, so the thickness is preferably 20-30μm; in addition, the porosity of the hydrophilic PTFE microporous membrane described in step A is 60-95%, and the pore size is 0.01-10μm. In order to ensure that the polymer slurry can fully penetrate into the microporous membrane, the porosity is preferably 80-90%, and the pore size is preferably 0.1-3μm.

[0015] Furthermore, the milky white casting solution described in step B is composed of an alkali-resistant polymer solution and inorganic nanoparticles, wherein the alkali-resistant polymer solution is composed of an organic solvent and an alkali-resistant polymer, the organic solvent is a combination of one or more of N-methylpyrrolidone, N,N-dimethylacetamide, and N,N-dimethylformamide, the alkali-resistant polymer is a combination of one or more of polysulfone, polyethersulfone, polyphenylsulfone, and polyphenylene sulfone, and the inorganic nanoparticles are a combination of one or more of zirconium dioxide, titanium dioxide, and aluminum oxide.

[0016] Furthermore, the contact angle between the other layer of hydrophilic PTFE microporous membrane described in step C and water is preferably 0°, and its thickness is 5~50μm. Because the upper PTFE microporous membrane will not be compressed by the polymer slurry, the thickness is preferably 15~25μm. At the same time, the porosity selection range is 60~95%, preferably 80~90%, and the pore size is 0.01~10μm, preferably 0.1~3μm, to ensure that the membrane surface has sufficient porosity and suitable pore size so that the casting liquid can be fully immersed.

[0017] Furthermore, the primary coagulation bath in step D is composed of pure water, the time of the primary coagulation bath is preferably 10 minutes, and the temperature is preferably 40° C. While ensuring the quality of the diaphragm, the present application can effectively improve production efficiency by shortening the primary coagulation bath time as much as possible, and the coagulation bath temperature close to room temperature is easier to achieve in production.

[0018] Furthermore, the secondary coagulation bath described in step E is composed of pure water, and the time of the secondary coagulation bath is preferably 30 minutes, and the temperature is preferably 25° C., so that the residual organic solvent is completely removed to prevent it from contaminating the alkali solution and flow channel in the electrolytic cell in actual application.

[0019] Also disclosed is an application of the sandwich structure water electrolysis composite diaphragm using the above sandwich structure or the sandwich structure water electrolysis composite diaphragm prepared by the above preparation method, and the composite diaphragm is used in the process of electrolyzing water to produce hydrogen.

[0020] Compared with the prior art, this method has the following excellent effects:

[0021] 1. The process of the present invention is simple and easy to repeat, the conditions are easy to meet, the application range is wide, and it can be used for the preparation of composite membranes for water electrolysis of all systems.

[0022] 2. The sandwich structure composite diaphragm of the present invention has excellent thermal stability, outstanding chemical corrosion resistance, air tightness, and excellent surface scratch resistance and tear resistance; the surface micropores and internal finger-shaped holes formed provide a three-dimensional continuous channel for ion migration of the diaphragm, the surface pore size on both sides is 1~5μm, and the internal pore size is less than 1μm, which effectively reduces the surface resistance of the diaphragm; at the same time, compared with the traditional composite diaphragm, the puncture resistance and elongation at break have been greatly improved, from 45N and 15.6% to 254.1N and 53.5%.

[0023] 3. Due to the assembly requirements of the electrolyzer, hydrophilic PTFE with appropriate thickness (100~400μm) cannot serve the hydrogen production membrane industry due to process or cost restrictions. However, the present invention uses a polytetrafluoroethylene porous membrane with a thickness of about 5~50μm and excellent mechanical properties and chemical stability at high temperature as the surface protection layer on both sides, and adds a slurry mixed with an alkali-resistant polymer and a hydrophilic filler in the middle layer to prepare a composite membrane with a sandwich structure, forming a structure with high puncture resistance, appropriate thickness, dense microscopic surface and rich micropores, which not only improves the mechanical strength of the membrane surface, but also facilitates the penetration of electrolyte solution (hydroxyl ions). At the same time, the thickness can be adjusted (100~600μm) to meet the application requirements of alkaline water electrolyzers for various aspects of the membrane (including thickness, mechanical properties, porosity, surface resistance, etc.). BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a layer structure diagram of a sandwich structure composite diaphragm;

[0025] Figure 2 is an enlarged view of the upper surface of the sandwich structure composite diaphragm in Example 3;

[0026] Figure 3 This is an enlarged view of the lower surface of the sandwich structure composite diaphragm in Example 3;

[0027] Figure 4 is a cross-sectional view of a sandwich structure composite diaphragm with a thickness of 250 μm prepared in Example 3;

[0028] Figure 5 is a cross-sectional view of a sandwich structure composite diaphragm with a thickness of 150 μm prepared in Example 8;

[0029] Figure 6 This is the contact interface diagram between the PTFE porous membrane and the intermediate layer. DETAILED DESCRIPTION

[0030] The invention is further described below in conjunction with the examples. It should be noted that the following examples are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Therefore, although the present invention has been described in detail in this specification with reference to the following examples, it should be understood by those skilled in the art that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

[0031] Unless otherwise specified, the raw materials described in the examples of the present invention are conventional raw materials available on the market, the equipment used are commonly used equipment in the field, the preparation conditions are normal conditions, and the identification of the products is identified by conventional methods.

[0032] Reference Figure 1 As shown, the present application proposes a sandwich structure electrolysis composite diaphragm, including a first layer, an intermediate layer and a third layer that are composited into one, the first layer is a PTFE / polymer / inorganic nanoparticle composite porous layer with a thickness of 5~50μm; the intermediate layer is a polymer / inorganic nanoparticle composite porous layer with a thickness of 100~400μm; the third layer is a PTFE / polymer / inorganic nanoparticle composite porous layer with a thickness of 5~50μm, the first layer and the third layer both use PTFE as a substrate, which has excellent surface scratch resistance and tear resistance, and also has good chemical corrosion resistance, the intermediate layer material has good hydrophilic properties and porous structure like the first layer and the third layer, so it has good bonding during the mutual penetration process, ensuring that the intermediate layer is not easily separated from the first layer and the third layer.

[0033] The middle layer is formed by a milky white casting liquid, which is composed of an alkali-resistant polymer solution and inorganic nanoparticles. The alkali-resistant polymer solution is composed of an organic solvent and an alkali-resistant polymer. The organic solvent is a combination of one or more of N-methylpyrrolidone, N,N-dimethylacetamide, and N,N-dimethylformamide. The alkali-resistant polymer is a combination of one or more of polysulfone, polyethersulfone, polyphenylsulfone, and polyphenylene sulfone. The inorganic nanoparticles are a combination of one or more of zirconium dioxide, titanium dioxide, and aluminum oxide.

[0034] Comparative Example 1

[0035] A: Dissolve 19.05 g of polysulfone resin in 100 g of N-methylpyrrolidone and stir for 4 h to obtain a uniformly dispersed polysulfone solution; then add 57.15 g of zirconium dioxide and continue stirring for 4 h until it is completely dispersed. Finally, degassing treatment is carried out by stirring at a low speed for 1 h to obtain a milky white casting solution; immerse a 170 μm thick PPS mesh cloth in the milky white casting solution, wait for 2 minutes and then take it out, and then use a scraper with a preset spacing of 300 μm to scrape and obtain a liquid wet film with a thickness of about 300 μm;

[0036] B: Put the liquid wet film together with the glass plate into a coagulation bath for 10 minutes at a temperature of 40°C to obtain a preliminarily solidified white film;

[0037] C: The white film obtained in step B was placed in a secondary coagulation bath of pure water for 30 minutes at a coagulation bath temperature of 25° C., and finally an alkaline water electrolysis composite diaphragm with a thickness of 250 μm was obtained.

[0038] The surface resistance of the composite membrane was measured by a homemade surface resistance test device and was 0.105Ω·cm 2The puncture resistance and elongation at break are 45N and 15.6% respectively.

[0039] Example 1

[0040] A: Spread the hydrophilic PTFE microporous membrane with a contact angle of 90° with water on a glass plate and fix it with a porous vacuum suction cup; the PTFE microporous membrane has a thickness of 30μm, a porosity of 90%, and a pore size of 3μm. The manufacturer is Suzhou Youkefa New Material Technology Co., Ltd., and the model is YKF-PM300-30.

[0041] B: The milky white casting solution prepared in Comparative Example 1 is horizontally coated on the PTFE microporous membrane of step A, and the preset spacing of the scraper is 300 μm;

[0042] C: Lay a hydrophilic PTFE microporous membrane with a contact angle of 90° with water on the white wet membrane obtained in step B. The PTFE microporous membrane has a thickness of 20μm, a porosity of 90%, and a pore size of 3μm. The manufacturer is Suzhou Youkefa New Material Technology Co., Ltd., and the model is YKF-PM300-20. Then use a scraper with a preset spacing (300μm) to scrape it flat and let it stand for 10s to obtain a liquid wet membrane with a thickness of 300μm;

[0043] D: The liquid wet film of the sandwich structure obtained in step C is placed together with the glass plate in a coagulation bath for 10 minutes, and the coagulation bath temperature is 40°C. After the composite film is separated from the glass plate, a white film is initially solidified;

[0044] E: The composite diaphragm prepared in step D is placed in a secondary coagulation bath of pure water for 30 minutes at a coagulation bath temperature of 25° C., and finally an alkaline water electrolysis sandwich structure composite diaphragm with a thickness of about 250 μm is obtained.

[0045] Example 2

[0046] A: Spread the hydrophilic PTFE microporous membrane with a contact angle of 45° with water on a glass plate and fix it with a porous vacuum suction cup; the PTFE microporous membrane has a thickness of 30μm, a porosity of 90%, and a pore size of 3μm. The manufacturer is Suzhou Youkefa New Material Technology Co., Ltd., and the model is YKF-PM300-30.

[0047] B: The milky white casting solution prepared in Comparative Example 1 is horizontally coated on the PTFE microporous membrane of step A, and the preset spacing of the scraper is 300 μm;

[0048] C: Lay a hydrophilic PTFE microporous membrane with a contact angle of 35° with water on the white wet membrane obtained in step B. The PTFE microporous membrane has a thickness of 20 μm, a porosity of 90%, and a pore size of 3 μm. The manufacturer is Suzhou Youkefa New Material Technology Co., Ltd., and the model is YKF-PM300-20. Then use a scraper with a preset spacing (300 μm) to scrape it flat and let it stand for 10 seconds to obtain a liquid wet membrane with a thickness of 300 μm;

[0049] D: The liquid wet film of the sandwich structure obtained in step C is placed together with the glass plate in a coagulation bath for 10 minutes, and the coagulation bath temperature is 40°C. After the composite film is separated from the glass plate, a white film is initially solidified;

[0050] E: The composite diaphragm prepared in step D is placed in a secondary coagulation bath of pure water for 30 minutes at a coagulation bath temperature of 25° C., and finally an alkaline water electrolysis sandwich structure composite diaphragm with a thickness of about 250 μm is obtained.

[0051] Example 3

[0052] A: Spread the hydrophilic PTFE microporous membrane with a contact angle of 0° with water on a glass plate and fix it with a porous vacuum suction cup; the PTFE microporous membrane has a thickness of 30μm, a porosity of 90%, and a pore size of 3μm. The manufacturer is Suzhou Youkefa New Material Technology Co., Ltd., and the model is YKF-PM300-30.

[0053] B: The milky white casting solution prepared in Comparative Example 1 is horizontally coated on the PTFE microporous membrane of step A, and the preset spacing of the scraper is 300 μm;

[0054] C: Lay a hydrophilic PTFE microporous membrane with a contact angle of 0° with water on the white wet membrane obtained in step B. The PTFE microporous membrane has a thickness of 20 μm, a porosity of 90%, and a pore size of 3 μm. The manufacturer is Suzhou Youkefa New Material Technology Co., Ltd., and the model is YKF-PM300-20. Then use a scraper with a preset spacing (300 μm) to scrape it flat and let it stand for 10 seconds to obtain a liquid wet membrane with a thickness of 300 μm;

[0055] D: The liquid wet film of the sandwich structure obtained in step C is placed together with the glass plate in a coagulation bath for 10 minutes, and the coagulation bath temperature is 40°C. After the composite film is separated from the glass plate, a white film is initially solidified;

[0056] E: The composite diaphragm prepared in step D is placed in a secondary coagulation bath of pure water for 30 minutes at a coagulation bath temperature of 25° C., and finally an alkaline water electrolysis sandwich structure composite diaphragm with a thickness of about 250 μm is obtained.

[0057] The upper surface structure of the alkaline water electrolysis sandwich structure composite diaphragm prepared in Example 3 is shown in FIG. Figure 2 As shown, the lower surface structure is as follows Figure 3 As shown, and its cross-sectional view is as Figure 4 As shown, it can be seen that during the preparation process, the diaphragm slurry (casting liquid) has fully penetrated into the PTFE porous membrane, giving the surface layer and the middle layer a strong interface bonding force, while ensuring the flexibility, scratch resistance and tear resistance of the diaphragm.

[0058] The surface resistance of the composite membranes prepared in Examples 1 to 3 measured by the surface resistance test device is 0.642 Ω·cm 2 、0.384Ω·cm 2 、0.075Ω·cm 2 , as shown in Table 1. This shows that the hydrophilicity of the membrane surface has a great influence on the membrane surface resistance. The better the hydrophilicity, the lower the membrane surface resistance. 2 The layer ensures high water content and porous channels inside the diaphragm, promoting ion transport during electrolysis.

[0059] Example 4

[0060] A: Spread the hydrophilic PTFE microporous membrane with a contact angle of 0° with water on a glass plate and fix it with a porous vacuum suction cup; the PTFE microporous membrane has a thickness of 20 μm, a porosity of 90%, and a pore size of 3 μm. The manufacturer is Suzhou Youkefa New Material Technology Co., Ltd., and the model is YKF-PM300-20.

[0061] B: The milky white casting solution prepared in Comparative Example 1 is horizontally coated on the PTFE microporous membrane of step A, and the preset spacing of the scraper is 300 μm;

[0062] C: Lay a hydrophilic PTFE microporous membrane with a contact angle of 0° with water on the white wet membrane obtained in step B. The PTFE microporous membrane has a thickness of 10μm, a porosity of 90%, and a pore size of 3μm. The manufacturer is Suzhou Youkefa New Material Technology Co., Ltd., and the model is YKF-PM300-10. Then use a scraper with a preset spacing (300μm) to scrape it flat and let it stand for 10s to obtain a liquid wet membrane with a thickness of 300μm;

[0063] D: The liquid wet film of the sandwich structure obtained in step C is placed together with the glass plate in a coagulation bath for 10 minutes, and the coagulation bath temperature is 40°C. After the composite film is separated from the glass plate, a white film is initially solidified;

[0064] E: The composite diaphragm prepared in step D is placed in a secondary coagulation bath of pure water for 30 minutes at a coagulation bath temperature of 25° C., and finally an alkaline water electrolysis sandwich structure composite diaphragm with a thickness of about 250 μm is obtained.

[0065] Example 5

[0066] A: Spread the hydrophilic PTFE microporous membrane with a contact angle of 0° with water on a glass plate and fix it with a porous vacuum suction cup; the PTFE microporous membrane has a thickness of 40μm, a porosity of 90%, and a pore size of 3μm. The manufacturer is Suzhou Youkefa New Material Technology Co., Ltd., and the model is YKF-PM300-40.

[0067] B: The milky white casting solution prepared in Comparative Example 1 was horizontally coated on the PTFE microporous membrane in step A, and the preset spacing of the scraper was 300 μm;

[0068] C: Lay a hydrophilic PTFE microporous membrane with a contact angle of 0° with water on the white wet membrane obtained in step B. The PTFE microporous membrane has a thickness of 30μm, a porosity of 90%, and a pore size of 3μm. The manufacturer is Suzhou Youkefa New Material Technology Co., Ltd., and the model is YKF-PM300-30. Then use a scraper with a preset spacing (300μm) to scrape it flat and let it stand for 10s to obtain a liquid wet membrane with a thickness of 300μm;

[0069] D: The liquid wet film of the sandwich structure obtained in step C is placed together with the glass plate in a coagulation bath for 10 minutes, and the coagulation bath temperature is 40°C. After the composite film is separated from the glass plate, a white film is initially solidified;

[0070] E: The composite diaphragm prepared in step D is placed in a secondary coagulation bath of pure water for 30 minutes at a coagulation bath temperature of 25° C., and finally an alkaline water electrolysis sandwich structure composite diaphragm with a thickness of about 250 μm is obtained.

[0071] The surface resistances of the composite diaphragms prepared in Example 4 and Example 5 were measured by a self-made surface resistance test device and were 0.072 Ω·cm 2 , 0.087Ω·cm 2, as shown in Appendix 2. When the PTFE thickness is 20μm for the first layer and 10μm for the third layer (Example 4), the puncture resistance and elongation at break are 193.5N and 45.7% respectively; when the PTFE thickness is 30μm for the first layer and 20μm for the third layer (Example 3), the puncture resistance and elongation at break are 254.1N and 53.5% respectively; when the PTFE thickness is 40μm for the first layer and 30μm for the third layer (Example 5), the puncture resistance and elongation at break are 272.1N and 55.2% respectively. This indicates that within a certain range (5~50μm), the thicker the PTFE thickness on the surface of the diaphragm, the higher the overall performance of the diaphragm including puncture resistance and elongation at break will be, but at the same time the surface resistance will also increase (intermediate PSU / ZrO 2 The thickness of the layer is reduced, the density of the finger-like pores decreases, and the internal porosity decreases). Therefore, the preparation of the corresponding diaphragm can be selected according to the design of the trough structure to give full play to the performance advantages of the diaphragm.

[0072] Example 6

[0073] A: Spread the hydrophilic PTFE microporous membrane with a contact angle of 0° with water on a glass plate and fix it with a porous vacuum suction cup; the PTFE microporous membrane has a thickness of 30μm, a porosity of 70%, and a pore size of 1μm. The manufacturer is Suzhou Youkefa New Material Technology Co., Ltd., and the model is YKF-PM100-30.

[0074] B: The milky white casting solution prepared in Comparative Example 1 was horizontally coated on the PTFE microporous membrane in step A, and the preset spacing of the scraper was 300 μm;

[0075] C: Lay a hydrophilic PTFE microporous membrane with a contact angle of 0° with water on the white wet membrane obtained in step B. The PTFE microporous membrane has a thickness of 20 μm, a porosity of 70%, and a pore size of 1 μm. The manufacturer is Suzhou Youkefa New Material Technology Co., Ltd., and the model is YKF-PM100-20. Then use a scraper with a preset spacing (300 μm) to scrape it flat and let it stand for 10 seconds to obtain a liquid wet membrane with a thickness of 300 μm;

[0076] D: The liquid wet film of the sandwich structure obtained in step C is placed together with the glass plate in a coagulation bath for 10 minutes, and the coagulation bath temperature is 40°C. After the composite film is separated from the glass plate, a white film is initially solidified;

[0077] E: The composite diaphragm prepared in step D is placed in a secondary coagulation bath of pure water for 30 minutes at a coagulation bath temperature of 25° C., and finally an alkaline water electrolysis sandwich structure composite diaphragm with a thickness of about 250 μm is obtained.

[0078] Example 7

[0079] A: Spread the hydrophilic PTFE microporous membrane with a contact angle of 0° with water on a glass plate and fix it with a porous vacuum suction cup; the PTFE microporous membrane has a thickness of 30μm, a porosity of 95%, and a pore size of 4μm. The manufacturer is Suzhou Youkefa New Material Technology Co., Ltd., and the model is YKF-PM400-30.

[0080] B: The milky white casting solution prepared in Comparative Example 1 was horizontally coated on the PTFE microporous membrane in step A, and the preset spacing of the scraper was 300 μm;

[0081] C: Lay the hydrophilic ePTFE microporous membrane with a contact angle of 0° with water on the white wet membrane obtained in step B. The PTFE microporous membrane has a thickness of 20μm, a porosity of 95%, and a pore size of 4μm. The manufacturer is Suzhou Youkefa New Material Technology Co., Ltd., and the model is YKF-PM400-20. Then use a scraper with a preset spacing (300μm) to scrape it flat and let it stand for 10s to obtain a liquid wet membrane with a thickness of 300μm;

[0082] D: The liquid wet film of the sandwich structure obtained in step C is placed in a coagulation bath together with the glass plate for 10 min. The coagulation bath temperature is 40°C. After the composite film is separated from the glass plate, a white film is initially solidified.

[0083] E: The composite diaphragm prepared in step D is placed in a secondary coagulation bath of pure water for 30 minutes at a coagulation bath temperature of 25° C., and finally an alkaline water electrolysis sandwich structure composite diaphragm with a thickness of about 250 μm is obtained.

[0084] As shown in Table 3, when the porosity of PTFE is 70% (Example 6), the maximum pore size on the membrane surface is 1 μm, and the bubble point pressure and surface resistance are 0.84 MPa and 0.091 Ω·cm, respectively. 2 When the PTFE porosity is 90% (Example 3), the maximum pore size on the membrane surface is 3 μm, and the bubble point pressure and surface resistance are 0.66 MPa and 0.075 Ω·cm, respectively. 2 When the PTFE porosity is further increased to 95% (Example 7), the maximum pore size on the membrane surface is 4 μm, and the bubble point pressure and surface resistance are 0.32 MPa and 0.071 Ω·cm, respectively. 2 The reason why the surface resistance does not decrease significantly when the porosity further increases to 95% is that most of the pores on the PTFE surface are filled with PSU / ZrO 2 The unfilled part has a larger pore size (~4μm), which leads to a gap in the bubble point and a decrease in the air tightness of the diaphragm. Therefore, the 90% porosity PTFE membrane can ensure that the surface resistance of the diaphragm is low enough when it has a higher bubble point.

[0085] Example 8

[0086] A: Spread the hydrophilic PTFE microporous membrane with a contact angle of 0° with water on a glass plate and fix it with a porous vacuum suction cup; the PTFE microporous membrane has a thickness of 30μm, a porosity of 90%, and a pore size of 3μm. The manufacturer is Suzhou Youkefa New Material Technology Co., Ltd., and the model is YKF-PM300-30.

[0087] B: The milky white casting solution prepared in Comparative Example 1 was horizontally coated on the PTFE microporous membrane in step A, and the preset spacing of the scraper was 200 μm;

[0088] C: Lay a hydrophilic PTFE microporous membrane with a contact angle of 0° with water on the white wet membrane obtained in step B. The PTFE microporous membrane has a thickness of 20μm, a porosity of 90%, and a pore size of 3μm. The manufacturer is Suzhou Youkefa New Material Technology Co., Ltd., and the model is YKF-PM300-20. Then use a scraper with a preset spacing (200μm) to scrape it flat and let it stand for 10s to obtain a liquid wet membrane with a thickness of 200μm;

[0089] D: The liquid wet film of the sandwich structure obtained in step C is placed together with the glass plate in a coagulation bath for 10 minutes, and the coagulation bath temperature is 40°C. After the composite film is separated from the glass plate, a white film is initially solidified;

[0090] E: The composite diaphragm prepared in step D is placed in a secondary coagulation bath of pure water for 30 minutes at a coagulation bath temperature of 25° C., and finally an alkaline water electrolysis sandwich structure composite diaphragm with a thickness of about 150 μm is obtained.

[0091] The cross-sectional view of the composite diaphragm is as follows: Figure 5 As shown, the sandwich structure is relatively uniform on a large scale, and the finger-like holes in the middle layer are widely distributed, which is beneficial to reducing the surface resistance of the diaphragm.

[0092] Example 9

[0093] A: Spread the hydrophilic PTFE microporous membrane with a contact angle of 0° with water on a glass plate and fix it with a porous vacuum suction cup; the PTFE microporous membrane has a thickness of 30μm, a porosity of 90%, and a pore size of 3μm. The manufacturer is Suzhou Youkefa New Material Technology Co., Ltd., and the model is YKF-PM300-30.

[0094] B: The milky white casting solution prepared in Comparative Example 1 was horizontally coated on the PTFE microporous membrane in step A, and the preset spacing of the scraper was 500 μm;

[0095] C: Lay a hydrophilic PTFE microporous membrane with a contact angle of 0° with water on the white wet membrane obtained in step B. The PTFE microporous membrane has a thickness of 20 μm, a porosity of 90%, and a pore size of 3 μm. The manufacturer is Suzhou Youkefa New Material Technology Co., Ltd., and the model is YKF-PM300-20. Then use a scraper with a preset spacing (500 μm) to scrape it flat and let it stand for 10 seconds to obtain a liquid wet membrane with a thickness of 500 μm;

[0096] D: The liquid wet film of the sandwich structure obtained in step C is placed together with the glass plate in a coagulation bath for 10 minutes, and the coagulation bath temperature is 40°C. After the composite film is separated from the glass plate, a white film is initially solidified;

[0097] E: The composite diaphragm prepared in step D is placed in a secondary coagulation bath of pure water for 30 minutes at a coagulation bath temperature of 25° C., and finally an alkaline water electrolysis sandwich structure composite diaphragm with a thickness of about 420 μm is obtained.

[0098] As shown in Appendix 4, when the thickness of the composite diaphragm is 150 μm (Example 8), 250 μm (Example 3), and 420 μm (Example 9), the surface resistance of the diaphragm is 0.058 Ω·cm 2 、0.075Ω·cm 2 、0.123Ω·cm 2 It can be seen that when the thickness is between 150 and 420 μm, the surface resistance increases with the increase of the thickness of the diaphragm; the puncture resistance is 153N, 254.1N, and 283.4N respectively; the bubble point pressure of the diaphragm is 0.47MPa, 0.66MPa, and 0.92MPa respectively. In summary, the composite diaphragm with a thickness of 250 μm in Example 3 has a low surface resistance (0.075Ω·cm 2 ), while still maintaining a high bubble point pressure (0.66MPa). Therefore, by adjusting the thickness (100~600μm), the application requirements of alkaline water electrolyzers for diaphragms in all aspects (including thickness, mechanical properties, porosity, surface resistance, etc.) can be met.

[0099] The comparison of the parameters of the diaphragms prepared in the above embodiments and the results of the related tests are shown in Appendix 1 to 4:

[0100] Appendix 1: Effect of hydrophilicity of PTFE porous membrane on surface resistance of composite diaphragm

[0101] Comparative Example 1 Example 1 Example 2 Example 3 Contact angle of the first layer of PTFE to water / 90° 45° 0° The contact angle of the third layer of PTFE to water / 90° 35° 0° Diaphragm surface resistance <![CDATA[0.105Ω·cm 2 ]]> <![CDATA[0.642Ω·cm 2 ]]> <![CDATA[0.384Ω·cm 2 ]]> <![CDATA[0.075Ω·cm 2 ]]>

[0102] Appendix 2: Effect of PTFE porous membrane thickness on the mechanical properties of composite diaphragms

[0103] Example 4 Example 3 Example 5 Thickness of the first layer of PTFE 20μm 30μm 40μm The thickness of the third layer of PTFE 10μm 20μm 30μm Diaphragm surface resistance <![CDATA[0.072Ω·cm 2 ]]> <![CDATA[0.075Ω·cm 2 ]]> <![CDATA[0.087Ω·cm 2 ]]> Puncture resistance 193.5N 254.1N 272.1N Elongation at break 45.7% 53.5% 55.2%

[0104] Appendix 3: Effect of PTFE porous membrane porosity on composite diaphragm performance

[0105] Example 6 Example 3 Example 7 PTFE Porosity 70% 90% 95% Maximum pore size on the surface 1μm 3μm 4μm Diaphragm bubble point pressure 0.84MPa 0.66MPa 0.32MPa Diaphragm surface resistance <![CDATA[0.091Ω·cm 2 ]]> <![CDATA[0.075Ω·cm 2 ]]> <![CDATA[0.071Ω·cm 2 ]]>

[0106] Appendix 4: Effect of overall thickness of composite diaphragm on performance

[0107] Example 8 Example 3 Example 9 Composite diaphragm thickness ~150μm ~250μm ~420μm Diaphragm surface resistance <![CDATA[0.058Ω·cm 2 ]]> <![CDATA[0.075Ω·cm 2 ]]> <![CDATA[0.123Ω·cm 2 ]]> Puncture resistance 153N 254.1N 283.4N Elongation at break 20% 53.5% 56.8% Diaphragm bubble point pressure 0.47MPa 0.66MPa 0.92MPa

[0108] In summary, the sandwich structure composite diaphragm of the present invention has excellent thermal stability, outstanding chemical corrosion resistance, air tightness, and excellent surface scratch resistance and tear resistance; the formed surface micropores and internal finger-like pores are conducive to the penetration of electrolyte solution (hydroxyl ions), and are suitable for alkaline water electrolyzers with zero-gap structures, meeting the requirements of alkaline water electrolyzers for diaphragms in various aspects (including thickness, mechanical properties, porosity, surface resistance, etc.). The bonding effect between the membrane layers in the sandwich structure composite diaphragm is good, and there is no obvious bonding defect between the layers at a large scale. Figure 6 As shown, the finger-like pores of the middle layer are widely distributed and relatively uniform, which effectively reduces the surface resistance of the diaphragm. In addition, the operation is convenient during the entire preparation process. After the white casting liquid is applied and the multi-layer structure is scraped and leveled, the white casting liquid can enter the micropores of the two layers of PTFE, thereby forming a PTFE / polymer / inorganic nanoparticle composite porous layer. This layer can not only greatly improve the surface mechanical strength of the diaphragm, but also facilitate the penetration of the electrolyte. At the same time, the infiltration of the slurry not only improves the permanent hydrophilicity of the surface of the three-layer sandwich structure diaphragm, but also forms a continuous interlocking structure between the upper and lower surfaces and the middle layer, greatly improving the bonding strength of the interface.

[0109] Regarding the above-mentioned hydrophilic PTFE microporous membrane, a PTFE microporous membrane is hydrophilically modified with potassium permanganate, and a potassium permanganate solution is prepared. The concentration of the potassium permanganate solution is 0.1%~1%. The PTFE microporous membrane is immersed in the potassium permanganate solution for 1-4 hours at a temperature of 30-60 degrees. Potassium permanganate reacts with the surface of the PTFE microporous membrane to form polar functional groups. According to the solution concentration, reaction time, and solution temperature, PTFE microporous membranes with different contact angles to water are prepared.

[0110] The parameters and commercial sources of the raw materials used in the above preparation process are as follows: 1. Polysulfone resin: purchased from BASF AG, model S6010, water absorption rate 0.8%, hygroscopicity 0.3%, viscosity number 81cm 3 / g, melt volume-flow rate is 30cm 3 / 10min, molecular weight is 60000D. 2. Zirconium dioxide: purchased from Shandong Guoci Functional Materials Co., Ltd., model GMZ-B6, white color, purity 99.9%, particle size 50~100nm, water content 0.40~0.60%, bulk density 0.35~0.40g / cm 3 .

[0111] Regarding the above-mentioned test methods, the surface resistance test refers to the area resistance in the general test method for basic properties of alkaline battery separators SJ / T 10171-2016, chapter 4.8. The puncture resistance test device for the puncture resistance test refers to the puncture resistance test device in the chapter 5.1 of the "Test method for puncture resistance of plastic film and sheeting" GB / T 37841-2019, and the test standard refers to the puncture test in the chapter 8.2 of the "Test method for puncture resistance of plastic film and sheeting" GB / T 37841-2019. The elongation at break test refers to the 10.2 strain calculation in the chapter 10.2 of the "Determination of tensile properties of plastics Part 1: General" GB / T 1040.1-2018, 10.2.1 Extensometer Determination of Strain.

[0112] The above embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Any equivalent substitution or change made by a person skilled in the art based on the present invention is within the protection scope of the present invention.

Claims

1. A method for preparing a sandwich structure water electrolysis composite diaphragm, characterized in that: The diaphragm includes a first layer, an intermediate layer and a third layer which are composited into one body. The first layer is a PTFE / polymer / inorganic nanoparticle composite porous layer with a thickness of 5 to 50 μm; the intermediate layer is a polymer / inorganic nanoparticle composite porous layer with a thickness of 100 to 400 μm; the third layer is a PTFE / polymer / inorganic nanoparticle composite porous layer with a thickness of 5 to 50 μm; The preparation method comprises the following steps: A: Lay the hydrophilic treated PTFE microporous membrane flat on a glass plate and fix the glass plate with a porous vacuum suction cup; B: horizontally coating the milky white casting solution on the PTFE microporous membrane in step A, with the coating scraper spacing being 200 to 600 μm, to obtain a white wet film; C: Another layer of hydrophilic treated PTFE microporous membrane is laid flat on the white wet membrane prepared in step B, and a scraper with a preset spacing of 200 to 600 μm is used to scrape the surface of the PTFE microporous membrane flat, and the surface is left to stand for 10 to 60 seconds to obtain a liquid wet membrane with a thickness of 200 to 600 μm; D: placing the liquid wet film obtained in step C together with the glass plate into a primary coagulation bath for 2 to 30 min, the temperature of the coagulation bath being 0 to 60°C, the liquid wet film and the glass plate being separated in the primary coagulation bath, and the liquid wet film being preliminarily solidified into a white film in the primary coagulation bath; E: placing the white film obtained in step D in a secondary coagulation bath for 5 to 30 min, the coagulation bath temperature is 10 to 60° C., and finally obtaining a water electrolysis composite diaphragm with a sandwich structure and a thickness of 150 to 500 μm; The PTFE microporous membrane described in step A has a contact angle with water of 0°, a thickness of 20 to 30 μm, a porosity of 80 to 90%, and a pore size of 0.1 to 3 μm; The milky white casting solution described in step B is composed of an alkali-resistant polymer solution and inorganic nanoparticles, wherein the alkali-resistant polymer solution is composed of an organic solvent and an alkali-resistant polymer, the organic solvent is one or more of N-methylpyrrolidone, N,N-dimethylacetamide, and N,N-dimethylformamide, the alkali-resistant polymer is one or more of polysulfone, polyethersulfone, and polyphenylsulfone, and the inorganic nanoparticles are one or more of zirconium dioxide, titanium dioxide, and aluminum oxide; The PTFE microporous membrane described in step C has a contact angle with water of 0°, a thickness of 15 to 25 μm, a porosity of 80 to 90%, and a pore size of 0.1 to 3 μm.

2. The method for preparing the sandwich structure water electrolysis composite diaphragm according to claim 1, characterized in that: The primary coagulation bath described in step D is composed of pure water, and the time of the primary coagulation bath is 10 min and the temperature is 40°C.

3. The method for preparing the sandwich structure water electrolysis composite diaphragm according to claim 1, characterized in that: The secondary coagulation bath described in step E is composed of pure water, and the time of the secondary coagulation bath is 30 minutes and the temperature is 25°C.

4. An application of a sandwich structure water electrolysis composite diaphragm prepared by the preparation method according to any one of claims 1 to 3, characterized in that: Used in the process of producing hydrogen by electrolysis of water.

Citation Information

Patent Citations

  • Porous composite membrane for hydrogen production by alkaline electrolyzed water and preparation method of porous composite membrane

    CN117604571A

  • Alkaline electrolyzed water composite diaphragm and preparation method thereof

    CN118007186A